Particulate organic matter (POM) measured on water bottle samples from June 2013 - October 2020 in the Kiel Fjord, Germany - Fabian Wolf; Renate Schütt; Martin Wahl (PANGAEA, 2021)
Five sites across the Kiel Fjord in the Baltic Sea (GEOMAR Pier: 54.330383 N 10.150683 E, Kiel Canal Entry: 54.361167 N, 10.162533 E, Falckenstein: 54.390217 N, 10.194983 E, Laboe: 54.405633 N, 10.209750 E, and Strande: 54.428267 N, 10.209267 E) were monitored biweekly from June 2013 until October 2020 (with some discontinuities in winter). At each station water samples from 2 m depth were taken (2013-2015: 240 mL per filter; 2016-2020: 500 mL per filter). The water samples were filtered over filters with different sizes (2013: Cellulose Filters with 0.2, 3 and 12 μm and 50 mm diameter; 8μm Filter with 47 mm diameter; 2014: Cellulose Filters with 3μm and 8μm and 47 and 50 mm diameter, respectively; 2015: Cellulose Filters with 8 μm and 50 mm diameter; 2016-2020: Glas Fiber Filters). Filters were dried and seston dry weight was measured. For the years 2016-2020 the filters were burned afterwards and the POM ash free dry weight was measured.